2021
DOI: 10.1038/s41419-021-04326-y
|View full text |Cite
|
Sign up to set email alerts
|

Lipophagy deficiency exacerbates ectopic lipid accumulation and tubular cells injury in diabetic nephropathy

Abstract: Autophagy-mediated lipotoxicity plays a critical role in the progression of diabetic nephropathy (DN), but the precise mechanism is not fully understood. Whether lipophagy, a selective type of autophagy participates in renal ectopic lipid deposition (ELD) and lipotoxicity in the kidney of DN is unknown. Here, decreased lipophagy, increased ELD and lipotoxcity were observed in tubular cells of patients with DN, which were accompanied with reduced expression of AdipoR1 and p-AMPK. Similar results were found in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 48 publications
0
43
0
Order By: Relevance
“…Renal tubular damage appears to have a key role in DN, according to growing evidence ( Han et al, 2021 ; Yang et al, 2021 ; Li et al, 2022 ), and mitochondrial abnormalities largely contribute to this process ( Xiang J. et al, 2022 ; Liu et al, 2022 ). Mitochondria is in a dynamic equilibrium of fission and fusion, which is called mitochondrial dynamics, and the dynamic balance is essential for maintaining normal mitochondrial structure, number, distribution, and function ( Youle and van der Bliek, 2012 ; Chan, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Renal tubular damage appears to have a key role in DN, according to growing evidence ( Han et al, 2021 ; Yang et al, 2021 ; Li et al, 2022 ), and mitochondrial abnormalities largely contribute to this process ( Xiang J. et al, 2022 ; Liu et al, 2022 ). Mitochondria is in a dynamic equilibrium of fission and fusion, which is called mitochondrial dynamics, and the dynamic balance is essential for maintaining normal mitochondrial structure, number, distribution, and function ( Youle and van der Bliek, 2012 ; Chan, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lipid-storage disorders, such as ELA, disrupt lipid homeostasis and cause a series of serious metabolic diseases. ELA in the tubular portion of the kidney induces lipotoxicity, which is considered a novel mechanism for the progression of DN [ 8 ]. Recent studies suggested that the management of lipid metabolism contributes to the treatment of this diabetic complication [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that, during DN, LDs accumulate in the tubular portion of the kidney, which is one of the main sites of DN lesions [ 7 ]. This lipid-storage disorder induces lipotoxicity by promoting inflammation, producing reactive oxygen species, and causing cell death [ 8 ]. The increasing knowledge on the association between ELA and DN has driven researchers to consider novel therapeutic strategies for DN that aim to regulate LDs, reverse lipid disorder, and maintain lipid homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the specific mechanism of fenofibrate on the DKD model, researchers found that fenofibrate induced autophagy and acted as an antioxidant via the AMPK pathway ( Sohn et al, 2017 ). In addition, researchers have experimentally demonstrated that the use of therapeutic agents and approaches such as mitoQ (mitochondria-targeted antioxidant) and NSC697923 inhibitor and t-AUCB (an inhibitor of soluble epoxide hydrolase) can slow down the progression of DKD by improving autophagy ( Xiao et al, 2017 ; Pontrelli et al, 2018 ; Jiang et al, 2020 ; Han et al, 2021 ; Liang et al, 2021 ; Zheng et al, 2021 ). In summary, autophagy plays an important role in maintaining the homeostasis and function of renal tubular epithelial cells.…”
Section: Dkd and Autophagymentioning
confidence: 99%